Relationship of hydration and fat mass loss in people who exercise in gyms Alameda Urbanization, Chosica, Lurigancho, Lima, 2013 - Centón Quispe, Elisban Vicente (2019)
Objective: determine the relationship between the level of hydration and fat mass loss in people who exercisein gyms urbanization La Alameda, Lima. Material and Methods: Descriptive, correlational, not experimentalequipment such as anthropometric measuring rod design, scale, tape measure, caliper and impedance meter,standardized by the National Center for Food and Nutrition (DINE), as table color scale used for Armstrongdetermining the level of dehydration. The sample consisted of 80 participants. Results: In the results relatedto the level of hydration occurred in 1.25%, 85% and 13.8% respectively of DHT. In addition, all participantsreduced their percentage of body fat. However, it was observed that in the first two weeks of no significantinfluence evaluation and in the remaining two had no influence. Conclusions: There is significant correlationbetween the two variables, also there are other variables that influence the loss of fat mass and power, intensity,time, type of exercise, gender and different types of metabolism.